ANALISIS PERSEDIAAN BAHAN BAKU BAWANG GORENG PADA UD. SRI REJEKI KOTA PALU - Nurmagefirah A. Nazir; Yulianti Kalaba; Dewi Sartika Laurencia Br. Manurung (Fakultas Pertanian, Universitas Tadulako, 2022)
The study aims to determine the economical order quantity (EOQ) for raw material purchases, as well as the safety stock, reorder point, and total inventory cost for the company's inventory. This study was conducted in the first half of 2022 at UD Sri Rejeki, a company located in Palu City, Indonesia. The study utilized both primary data (collected from three respondents, including one leader and two employees) and secondary data. The analytical tool used in this study were EOQ, Safety Stock, Reorder Point, and Total Inventory Cost. The findings revealed that there were an average of 2.519,78 economy purchases (EOQ) of local shallot raw materials from January to December 2021, IDR 179,462,26 in total inventory costs (TIC), 1.656,31 kg in safety stock that must always be present in the warehouse to satisfy raw material shortages. UD Sri Rejeki has a relatively stable demand for local shallot raw materials throughout the year, with an average local shallot of 2.519,78 kg economy purchases (EOQ) required to meet their needs. The findings also showed that UD Sri Rejeki incurred IDR 179,462,26 in inventory costs from January to December 2021. To manage inventory levels, the company has set a safety stock of 1.656,31 kg that must always be present in the warehouse to ensure that they can satisfy any unexpected raw material shortages